Pension Funding Calculation Using the Benefit Prorate Method of the Constant Percent Type and Vasicek Interest Rates: Pension Fund Using Vasicek Model Based-Interest Rate - Khafifa , Laili Nur; Julianty, Dila Tirta; Listiani, Amalia (Enthusiastic : International Journal of Applied Statistics and Data Science, 2025)
Pension funds are financial programs established by individuals or companies to secure the future of employees by providing benefits during their retirement years. Pension funds are built up through contributions made by both the participants (employees) and the employer. To calculate the amount of pension benefits, normal costs, and actuarial liabilities, various method are used, including the constant percent benefit prorate method. A key factor influencing these calculations is the interest rate. This study employs the Vasicek model, a stochastic interest rate model, to analyze the Unfunded Actuarial Liability (UAL). The analysisi reveals that the amount of normal cost (annual contributions) will vary, and both contributions and actuarial liabilities that are calculated using vasicek interest rate for each participant will adjust based on the interest rate during their retirement period. The amount of UAL is derived from the discrepancy between the total amount of actuarial liabilities from all the participant in certain period and the accumulated funds. The UAL is sufficient to cover future pension fund payments when calculated using the Vasicek interest rate model.